Sustainable Cacao Agritourism Development Strategy for Cau Chocolate Bali - Putu Yudika Budi Kusuma; I Wayan Agus Selamet (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
While agritourism plays a crucial role in diversifying the income of cacao farmers in Bali, the sector still faces serious challenges including management inefficiencies and volatile market fluctuations. Cau Chocolate Bali is currently confronting real-world issues such as a significant decline in visitor numbers and cash flow stagnation due to suboptimal marketing strategies and a lack of innovation in tour packages. This condition creates an urgent need for strategic evaluation to ensure the destination can survive and compete in the sustainable tourism market. This study aims to formulate an agritourism development strategy for Cau Chocolate Bali using a sequential explanatory mixed-methods approach. Data were collected from 35 stakeholders through observation, in-depth interviews, and structured questionnaires, which were then analyzed using the Internal Factor Analysis Summary (IFAS) matrix, External Factor Analysis Summary (EFAS) matrix, Internal-External (IE) Matrix, and SWOT analysis. The results showed an IFAS score of 3.004 and an EFAS score of 2.513, positioning Cau Chocolate Bali in the